Effect of ginger root on cyclooxygenase-1 and 15-hydroxyprostaglandin dehydrogenase expression in colonic mucosa of humans at normal and increased risk of colorectal cancer - Jiang, Yan (2013)
OBJECTIVES: Elevated tissue levels of prostaglandin E(2) (PGE(2)), produced by cyclooxygenase (COX) are an early event in colorectal cancer (CRC). Data suggest the efficacy of non-steroidal anti-inflammatory (NSAIDs) drugs, which inhibit COX activity, as cancer preventives; however, side effects of NSAIDs indicate unacceptable limitations. Ginger has been reported to have anti-inflammatory activities with significant CRC preventive potential. We investigated if consumption of 2.0 g ginger daily regulated the level of two key enzymes, which control PGE(2) production, COX-1 and NAD(+)- dependent 15-hydroxyprostaglandin dehydrogenase (15-PGDH). METHODS: Thirty participants at normal and twenty participants at increased risk of CRC were randomized and given 2.0 g/day ginger or placebo for 28 days. Flexible sigmoidoscopy was used to obtain colon biopsies at baseline and end of the study. Tissue level of COX-1 and 15-PGDH were assessed using Western Blotting. RESULTS: After ginger consumption participants at increased risk of CRC, had significantly reduced colonic COX-1 protein level (23.8%± 41) compared to the placebo group (18.9%± 52; p=0.03). Protein levels of 15-PGDH in the colon were unchanged. In normal risk for CRC participants, neither protein levels of COX-1 nor 15-PGDH in the colon were altered by ginger consumption. CONCLUSION: Ginger significantly lowered COX-1 protein expression in increased risk participants, but not in normal risk participants at normal for CRC. Ginger did not alter 15-PGDH protein expression in either increased or normal risk participants. Further investigation, in larger studies with a longer ginger intervention is needed to examine the ability of ginger to impact tissue level of prostaglandin.